2006
DOI: 10.1093/ndt/gfl555
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of adhesion molecule expression in glomerular endothelial cells by anti-myeloperoxidase antibody

Abstract: These results showed that anti-MPO antibody activates not only neutrophils, but also GEC, indicating that anti-rmMPO IgG-induced direct activation of GEC contributes to neutrophil adhesion to GEC, thereby increasing glomerular neutrophil infiltration in initiation and progression of pauci-immune glomerulonephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…Especially in kidney, immunohistochemical staining showed that neutrophils located around the fringe of glomeruli with the development of mesangiolysis. To support this, we have previously reported that MPO-ANCA directly bound to primary glomerular endothelium following upregulation of ICAM-1, VCAM-1, E-selectin, and promotion of TNF-α production (35). These results are consistent with the observation of Little et al (31) that MPO-ANCA on leukocytes interacts with vascular endothelium via ICAM-1 in systemic vasculitis rats with developed MPO-ANCA.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Especially in kidney, immunohistochemical staining showed that neutrophils located around the fringe of glomeruli with the development of mesangiolysis. To support this, we have previously reported that MPO-ANCA directly bound to primary glomerular endothelium following upregulation of ICAM-1, VCAM-1, E-selectin, and promotion of TNF-α production (35). These results are consistent with the observation of Little et al (31) that MPO-ANCA on leukocytes interacts with vascular endothelium via ICAM-1 in systemic vasculitis rats with developed MPO-ANCA.…”
Section: Discussionsupporting
confidence: 86%
“…This is consistent with our previous results that MPO-ANCA was directly bound with glomerular endothelium and upregulated some adhesion molecules, including ICAM-1, VCAM-1, and Eselectin (35). In contrast, ANCA-QD was highly accumulated to the CD11b ϩ macrophage cluster in lung inflammatory lesion (Fig.…”
Section: Qd-conjugated Mpo-anca Are Detected On Activated Neutrophilssupporting
confidence: 93%
“…[125][126][127][128] In vitro studies show that cytokines, released in response to infections, prime neutrophils and upregulate adhesion molecules on neutrophils and endothelial cells (L and E selectins, respectively) to facilitate localization in glomerular capillaries. 129,130 Cytokine-primed neutrophils redistribute cytoplasmic primary granules containing MPO and PR3 to the cell surface where ANCA IgG binds directly or through Fc, Fab'2, or neutrophil-specific Mac-1 receptors activating a respiratory burst with release of cationic MPO and PR3 as well as other proteases and oxidants. [129][130][131][132][133][134][135] Neutrophil extracellular traps (NETs) are also formed containing entrapped MPO, PR3, and MPO DNA in a chromatin web and these can mediate injury directly through TLRs as well as modulate the immune response.…”
Section: T Cellsmentioning
confidence: 99%
“…129,130 Cytokine-primed neutrophils redistribute cytoplasmic primary granules containing MPO and PR3 to the cell surface where ANCA IgG binds directly or through Fc, Fab'2, or neutrophil-specific Mac-1 receptors activating a respiratory burst with release of cationic MPO and PR3 as well as other proteases and oxidants. [129][130][131][132][133][134][135] Neutrophil extracellular traps (NETs) are also formed containing entrapped MPO, PR3, and MPO DNA in a chromatin web and these can mediate injury directly through TLRs as well as modulate the immune response. 134,136 In ANCA-GN, NETs are present in the circulation and in glomeruli co-localized with neutrophils and DCs, and anti-NET antibodies are present along with circulating MPO-DNA complexes (nucleosomes).…”
Section: T Cellsmentioning
confidence: 99%
“…Because ANCA-associated glomerulonephritis could be diagnosed only with a positive ANCA titer and signs of nephritis (such as active urinary sediment and elevated serum creatinine), if we knew in advance that nearly 100% of patients would receive aggressive therapy after the histologic diagnosis by KBx, we could consider KBx not necessary for a diagnosis of ANCA-associated glomerulonephritis. In fact, since Nagao et al reported that anti-MPO antibody directly activated glomerular endothelial cells 14) , it was highly possible that the patients with abnormal urinary findings had ANCAassociated glomerulonephritis if serum ANCA, particularly MPO-ANCA, was positive. In addition, histopathologic classification of ANCA-associated glomerulonephritis has been shown to predict survival differences, but KBX-based therapeutic strategies have not been explored 15) .…”
Section: Discussionmentioning
confidence: 99%